ระบบคอมพิวเตอร์เพื่อการจัดสรรรถบรรทุก แบบพลวัตรภายใต้สภาวะความไม่แน่นอน - ปิยาพร โชตินันทกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The objective of this research is to develop a computerized system for stochastic dynamic truck allocation applying a readily available methodology. The methodology, which was initially developed in the late 1980’s and was continuously improved during the 1990’s, attempted to optimize the positioning of available trucks in a multi-terminal truckload network under uncertain demand. This research employs this methodology and develops a corresponding spreadsheet system that can be used on a daily basis to assist truckload dispatchers in simultaneously deciding on a given day how to assign trucks to known loads and how to reposition trucks for the next day assignment. Given a data set supplied by a truckload company in Thailand, the system is validated and the analysis results generated by the model reveal that the decisions recommended by the system can lead to a more effective truck allocation than the typical real-world practice that totally ignores the randomness in customer demands.